(untitled) (Sociología y tecnociencia, 2021)
According to various studies and surveys, religion, far from declining, plays an increasingly important role in the lives of the world’s citizens (this article analyses the differences by region, as well as the criteria for considering a society as secular). However, the way in which this influence has become apparent has changed from the past, as new religiosities, other ways of understanding and living spirituality, and some "substitutes" for religion have appeared, acting, nevertheless, with similar tools. The existential void caused by the failure of the great collective enterprises of the 20th century (communism, liberal capitalism, development cooperation, globalisation) led, on the one hand, to an increase in the individualistic search for happiness and, on the other, to a renewed interest in "spiritual matters". The Spirit of Silicon Valley responded to both needs by proposing itself as the solution to all problems. This new narrative, apparently secular, but with many features drawn from messianism, while rooted in the American tradition, is now being exported and consumed worldwide as a way of filling the void left by the lack of spiritual concepts. This article explores both the origins of this ideology of "salvation" and how it has spread around the globe.